Recombinant O-mannosylated protein production (PstS-1) from Mycobacterium tuberculosis in Pichia pastoris (Komagataella phaffii) as a tool to study tuberculosis infection - Giroshi Bando-Campos; Daniel Juárez-López; Sergio A. Román-González; Antonia I. Castillo-Rodal; Clarita Olvera; Yolanda López-Vidal; Roberto Arreguín-Espinosa; Clara Espitia; Mauricio A. Trujillo-Roldán; Norma A. Valdez-Cruz (Microbial Cell Factories, 2019)
Abstract Background Pichia pastoris (syn. Komagataella phaffii) is one of the most highly utilized eukaryotic expression systems for the production of heterologous glycoproteins, being able to perform both N- and O-mannosylation. In this study, we present the expression in P. pastoris of an O-mannosylated recombinant version of the 38 kDa glycolipoprotein PstS-1 from Mycobacterium tuberculosis (Mtb), that is similar in primary structure to the native secreted protein. Results The recombinant PstS-1 (rPstS-1) was produced without the native lipidation signal. Glycoprotein expression was under the control of the methanol-inducible promoter pAOX1, with secretion being directed by the α-mating factor secretion signal. Production of rPstS-1 was carried out in baffled shake flasks (BSFs) and controlled bioreactors. A production up to ~ 46 mg/L of the recombinant protein was achieved in both the BSFs and the bioreactors. The recombinant protein was recovered from the supernatant and purified in three steps, achieving a preparation with 98% electrophoretic purity. The primary and secondary structures of the recombinant protein were characterized, as well as its O-mannosylation pattern. Furthermore, a cross-reactivity analysis using serum antibodies from patients with active tuberculosis demonstrated recognition of the recombinant glycoprotein, indirectly indicating the similarity between the recombinant PstS-1 and the native protein from Mtb. Conclusions rPstS-1 (98.9% sequence identity, O-mannosylated, and without tags) was produced and secreted by P. pastoris, demonstrating that this yeast is a useful cell factory that could also be used to produce other glycosylated Mtb antigens. The rPstS-1 could be used as a tool for studying the role of this molecule during Mtb infection, and to develop and improve vaccines or kits based on the recombinant protein for serodiagnosis.